2018
DOI: 10.1007/s11356-018-3197-2
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and plant-derived compounds as eco-friendly agents to inhibit microbial toxins in poultry feed: a comprehensive review

Abstract: Some of pathogenic bacteria and fungi have the ability to produce fetal toxins which may be the direct causes of cytotoxicity or cellular dysfunction in the colonization site. Biological and non-biological environmental factors, challenge and microbes influence the effect of toxins on these pathogens. Modern research mentions that many natural materials can reduce the production of toxins in pathogenic microbes. However, researches that explain the mechanical theories of their effects are meager. This review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 129 publications
1
24
0
Order By: Relevance
“…The B. serrata essential oil has plentiful attributes of interest, comprising anti-bacterial, anti-fungal, anti-inflammatory, anti-tumor, and anti-oxidant activities as well as immunostimulatory agent, and it was successfully used as natural feed additive for poultry (5,6,8,9,20); however, there is a lack of information on the use of this medicinal plants in rabbit. Generally, medicinal plants and their secondary metabolites have been used for improving the efficiency and productivity of livestock production (1,21). The present study showed beneficial impacts of dietary BS supplementation on the LBW and BWG of growing rabbits.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The B. serrata essential oil has plentiful attributes of interest, comprising anti-bacterial, anti-fungal, anti-inflammatory, anti-tumor, and anti-oxidant activities as well as immunostimulatory agent, and it was successfully used as natural feed additive for poultry (5,6,8,9,20); however, there is a lack of information on the use of this medicinal plants in rabbit. Generally, medicinal plants and their secondary metabolites have been used for improving the efficiency and productivity of livestock production (1,21). The present study showed beneficial impacts of dietary BS supplementation on the LBW and BWG of growing rabbits.…”
Section: Discussionsupporting
confidence: 58%
“…The use of a 0.25-0.75 g/kg diet of BS the rabbit diets enhanced the feed consumption and efficiency. Previous studies have been shown the similar positive impact of phytogenic feed additives in animal production (1,4,8,9,21). The enhancement in LBW and BWG by BS, as a natural growth promoter, may be attributed to the presence of some active compounds (such as boswellic acid) which stimulates the ability to absorb and digest nutrients (5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 88%
“…Ashayerizadeh et al (), Alagawany (, ) and Abd El‐Hack (, ) recommended that probiotics and prebiotics could be used as alternatives to antibiotic growth promoters because they are free of harmful side effects to consumers, in addition to their ability to improve broiler chickens' growth indices. Li et al () showed that FCR was improved in laying ducks fed a diet supplemented with a Bacillus probiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics have many benefits to the host mainly through improving and/or strengthening the immune system [16]. They improve the efficiency of intestinal absorption of food by absorbing aflatoxin from the diet [19]. As the results of the present study indicated, Toxeat ® can alleviate suppressive and stressful effects that aflatoxin has on chickens.…”
Section: Discussionmentioning
confidence: 63%
“…Weight gain (g/bird) Feed intake(g/bird) FCR Livability % of aflatoxicosis [19]. LAB-containing Toxeat ® increased LAB levels in the cecum.…”
Section: Trtmentioning
confidence: 99%